Mathsoc: Sebuah media pembelajaran berbasis problem based learning - Siti Mulia Ristari; Heris Hendriana; Siti Chotimah (IKIP Siliwangi, 2026)
This study aims to develop a learning media assisted by Articulate Storyline software based on Problem Based Learning, and to find out its validity, feasibility, and effectiveness in improving students' mathematical critical thinking ability. This type of research uses Research and Development with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 6 students from class VII C in a limited trial, and 36 students from class VII H in one of Cimahi city's junior high schools for implementation. The instruments used for data collection included expert validation sheets, readability questionnaires, and mathematical critical thinking ability tests in the form of Pretests and Posttests. Data analysis techniques used descriptive and inferential analysis. The research findings showed that the media met the criteria for being very valid with an average media expert percentage of 92.4% and content expert of 93.85%, as well as a very good readability level of 92.17%. The media was declared suitable and effective in improving mathematical critical thinking ability with an N-gain value of 0.95 in the high category. Therefore, the MathSoc learning media is considered valid, suitable, and effective to use.